Blastobasis tarda Meyrick, 1902 an alien species from Australia new to Italy (Lepidoptera: Blastobasidae) - Manuela Pinzari; Mario Pinzari (SHILAP)
Blastobasis tarda Meyrick, 1902, an alien species from Australia was found for the first time in Italy.